The Evaluation of the Success about House Nutrition in Improvement Nutrition Status in Semarang - Hasana, Dien; Baitul Mukarromah, Siti (Public Health Perspective Journal, 2019)
Nutrition is an important factor that directly affects the quality of human resources, health problems and childhood nutrition is a major factor inhibiting the achievement of quality generation. Profile data Semarang City Health Office (2017), cases of malnutrition children year 2013-2016 showed a rising trend. Semarang City Health Office have children malnutrition treatment programs in a comprehensive manner, ie checks and supplementary feeding for malnourished children under five in the "House of Nutrition", but from the years 2014-2017, malnutrition children cared for street at House Nutrition Semarang City Health Office just less than 30% improved nutritional status. This study aimed to evaluate the program that has been done, in an effort to improve the nutritional status of children being treated at the Nutrition Semarang with the implementation of a comprehensive health examination program against malnutrition children. This research is a qualitative descriptive study. Selection of informants using purposive sampling technique and snowball sampling. The collection of data by observation using observation, in-depth interviews using interview guides, as well as data from medical records of patients. Analysis of data using qualitative descriptive analysis. as well as data from medical records of patients. Analysis of data using qualitative descriptive analysis. Program improvement of malnutrition at Home Nutrition Semarang implemented by examination of outpatient comprehensively for 6 months, including anthropometric measurements, determining the nutritional status, provision of F-100 during the inspection and the package to take home, a medical examination by a doctor, medical examination and performed stimulation of early detection and intervention of child development, physiotherapy, counseling and demos nutrition, administration high-calorie high-protein snacks, as well as vitamins and drugs has been running well, only need to be improved in the provision of nutritional counseling and family counseling. Increased IEC necessary for parents of toddlers so that there is a commitment to implement a whole series of checks and recommended by doctors and officers well.